Brand Loyalty of Women Consumers with Respect To FMCGs - Kamalaveni, D.K.; Rajalakshmi, S.; Kalaiselvi, S. (Indian Journal of Marketing, 2008)
Marketing starts with the determination of consumers wants and ends with the satisfaction of those wants. Every company must be organized totally around the marketing function, anticipating, stimulating and meeting customer’s requirements. Advertising in India has grown in a spectacular manner throughout the last two decades and has scaled new peaks during the last ten years in terms of size, range and quality. Over the years, there has also been a substantial expansion in the media. Everything the purchaser gets in exchange for his money is the product. Product has its personality. Four elements surround the product concept viz., branding, packing and labeling product warranty and service. Branding is an essential part of marketing sub-function of selling. Every manufacturer feels the need of identifying his goods with some definite symbol, mark or slogan, so that his goods catch the attention of the customers. Branding is invariably used to introduce "Product differentiation" in the market, to single out a product from its rivals. This paper highlights the brand loyalty of women consumers in respect of eight categories of FMCGs that are commonly used by both urban and rural consumers.